The Antioxidant Effectivity of Combination Banana Peel Extract and Orange Peel Extract - Ramadhani Dwi Sula; Ulil Fikri Nurhakimah; Elma Arifatul Sugito; Ika Trisharyanti Dian Kusumowati (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Oxidation reactions on foods and drugs can be inhibit by using antioxidants that binding to free radicals and reactive molecules. The Ambonese banana (Musa paradisiaca) peel and orange (Citrus reticulata) peel have antioxidant activity potency. The aim of this research is knowing the antioxidant activity of combination Ambonese banana (Musa paradisiaca) peel and orange (Citrus reticulata) peel. IC50 for antioxidant activity potency between Ambonese banana (Musa paradisiaca) peel and orange (Citrus reticulata) peel is expected to increase the antioxidant activity if used as combination that can inhibit oxidation reaction. The inhibit concentration of antioxidant activity is indicated by IC50. The compound that has the highest antioxidant activity will show lowest level of IC50. The antioxidant activity test was performed by DPPH method using UV-Vis spectrophotometer on 516 nm and color change of DPPH from purple to yellow when both of them react with antioxidant compound. The results of IC50 of banana peel extract was 114 mcg / mL; IC50 of orange peel extract was22.2 mcg / mL. The greatest inhibition of the combination of both extracts was 73.53% consisting of 25 Î¼L (0,005%) sample of tangerine orange peel extract and 75 Î¼L (0,015%).The biggest inhibition of the combination of both extracts was 73.53% consisting of 25 Î¼L (0.005%) samples of tangerine orange peel extract and 75 Î¼L (0.015%).